High performance MXene-based fibers and preparation methods thereof

The titanium carbide/(PEDOT:PSS)/polyrothane composite fibers prepared and chemically crosslinked by wet spinning method to form a dynamic roller-skating interface and a rigid interface, solving the shortcomings of high-performance titanium carbide composite conductive fibers in terms of mechanical and electrical conductivity, and achieving high performance improvement of MXene-based fibers.

CN118547396BActive Publication Date: 2025-04-18NANKAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410766025.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-14
Publication Date
2025-04-18
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

High-performance titanium carbide composite conductive fibers perform poorly in mechanical toughness, structural stability, conductivity and conductivity retention, limiting their application in electronic fabrics.

Method used

Wet spinning method is used to prepare primary titanium carbide/(PEDOT:PSS)/polyrothane composite fibers, and a dynamic roller-skating interface and rigid interface are formed through chemical cross-linking and electrostatic coupling, followed by hot pressing and vacuum drying to optimize the fiber structure.

Benefits of technology

The high tensile strength, toughness, conductivity and conductivity retention of MXene-based fibers are achieved, giving the fiber excellent tensile stability and flexibility, and are suitable for the preparation of multifunctional ultra-high conductive composite fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118547396B_ABST
    Figure CN118547396B_ABST
Patent Text Reader

Abstract

The present application discloses a high-performance MXene-based fiber and a preparation method thereof, and belongs to the field of functional fiber technology. The preparation method of the present application includes: wet spinning a mixed dispersion containing titanium carbide, (PEDOT:PSS) and polyrotaxane, and making the spinning primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber chemically crosslinked in an organic solvent containing N,N′-carbonyldiimidazole and electrostatically coupled in a cleaning bath, hot pressing and vacuum drying to obtain high-performance MXene-based fibers. The preparation method of the present application can construct a multi-structure synergistic titanium carbide / PEDOT / polyrotaxane composite fiber with obvious wrinkle structure, adjustable porous structure, titanium carbide / polyrotaxane dynamic roller skating interface structure and titanium carbide / PEDOT rigid interface structure, thereby achieving ultra-high tensile strength, elongation at break, flexibility, excellent tensile stability, conductivity and conductivity retention rate after cyclic strain of MXene-based fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of functional fiber technology, and in particular, relates to a high-performance MXene-based fiber and a preparation method thereof. Background Art

[0002] Two-dimensional titanium carbide sheets show great promise for the preparation of high-strength and high-toughness conductive fibers due to their excellent mechanical and electrical properties and rich surface functional groups. However, traditional titanium carbide fibers generally have difficulty in combining mechanical strength and toughness, high conductivity and structural stability, which greatly limits their application in electronic fabrics. Therefore, the development of titanium carbide functional fibers that combine mechanical strength and toughness, high conductivity and structural stability has attracted much attention.

[0003] The patented technology with announcement number CN 115537972 B discloses a method for preparing a mechanically interlocked high-performance titanium carbide composite conductive fiber. The method prepares a primary titanium carbide / polyrotaxane composite fiber by wet spinning a liquid crystal dispersion containing titanium carbide and polyrotaxane, and then sequentially performs heat stretching and chemical cross-linking to form a conductive rigid network and a mechanical interlocking structure inside the fiber, thereby achieving improvements in the mechanical strength, toughness, conductivity and structural stability of the titanium carbide functional fiber.

[0004] However, the high-performance titanium carbide composite conductive fiber mentioned above has the following defects: First, the stress that can be dissipated by the wheel-slip effect generated by a single mechanical interlocking structure is limited, and it is difficult to withstand greater stress and deformation, resulting in low mechanical strength and structural stability of the titanium carbide composite conductive fiber; Second, the intrinsic conductivity of the high-performance titanium carbide composite conductive fiber needs to be improved, especially after multiple stretching cycles, the conductive rigid network is severely damaged, and the structural integrity of the fiber cannot be maintained, resulting in a relatively low conductivity retention rate, which limits its application in high-performance electronic fabrics. Summary of the invention

[0005] The present application discloses a high-performance MXene-based fiber and a preparation method thereof, aiming to solve the technical problems of the high-performance titanium carbide composite conductive fiber mentioned above in terms of maximum mechanical strength and toughness, structural stability, intrinsic conductivity and low conductivity retention rate.

[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a method for preparing high-performance MXene-based fibers, the preparation method comprising the following steps:

[0007] Wet spinning a mixed dispersion containing titanium carbide, (PEDOT:PSS) and polyrotaxane to obtain primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers;

[0008] The primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber is chemically cross-linked in an organic solvent containing N,N′-carbonyldiimidazole to obtain a MXene-based fiber with a dynamic roller-slip interface structure;

[0009] The MXene-based fiber with a dynamic roller-skating interface structure is electrostatically coupled in a cleaning bath, and then hot-pressed and vacuum-dried in sequence to obtain a high-performance MXene-based fiber.

[0010] In some embodiments, the polyrotaxane is one or more of polyisoprene / α-cyclodextrin, poly(ethylene glycol) / α-cyclodextrin, poly(propylene oxide) / α-cyclodextrin, poly(ethylene oxide) / α-cyclodextrin, N-[tris(hydroxymethyl)methyl]acrylamide / α-cyclodextrin, or 2-hydroxyethyl methacrylate / α-cyclodextrin;

[0011] In some embodiments, the coverage of the α-cyclodextrin is 0.2-10%.

[0012] In some embodiments, when the primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber is chemically cross-linked in an organic solvent containing N,N′-carbonyldiimidazole, the temperature is controlled at 50 to 80° C. and the time is 10 to 60 minutes.

[0013] In some embodiments, the mass fraction of the N,N′-carbonyldiimidazole in the organic solvent is 0.3 to 8 wt %.

[0014] In some embodiments, the electrostatic coupling time of the MXene-based fiber having a dynamic roller-sliding interface structure in the cleaning bath is controlled to be 10 to 50 minutes.

[0015] In some embodiments, the cleaning bath is any one of a dimethyl sulfoxide solution, a methanol solution, a 0.1-5 M sulfuric acid aqueous solution, and a methanol / ethanol mixed solution.

[0016] In some embodiments, the hot pressing is performed at a temperature of 40 to 120° C., a hot pressing pressure of 0.5 to 15 kPa, and a holding time of 3 to 30 minutes.

[0017] In some embodiments, the vacuum drying is performed at a temperature of 90 to 180° C. and for a time of 20 to 100 minutes.

[0018] The second aspect of the present application provides a high-performance MXene-based fiber prepared according to the preparation method described in the first aspect of the present application. The high-performance MXene-based fiber of the present application has at least one of the following characteristics:

[0019] Tensile strength ≥750MPa; Toughness ≥90MJ / m 3;

[0020] Young's modulus ≤3.5GPa; elongation at break ≥20%;

[0021] Conductivity ≥2500S / cm.

[0022] The third aspect of the present application provides the use of the high-performance MXene-based fibers prepared in the present application for preparing multifunctional ultra-high conductive composite fibers.

[0023] The fourth aspect of the present application provides a method for preparing a multifunctional ultra-high conductive composite fiber, the preparation method comprising the following steps:

[0024] The high-performance MXene-based fiber is immersed in a 0.2-3 wt% metal nanowire solution, and then taken out and dried to obtain an ultra-high conductive composite fiber;

[0025] Coating a polymer protective layer on the surface of the ultra-high conductive composite fiber to obtain a multifunctional ultra-high conductive composite fiber;

[0026] Wherein, the ultra-high conductive composite fiber has at least one of the following characteristics:

[0027] Conductivity is 100000~120000S / cm;

[0028] The conductivity retention after 200,000 stretching cycles is >95%.

[0029] In some embodiments, the metal nanowires are one or a combination of gold nanowires, silver nanowires, copper nanowires, or platinum nanowires.

[0030] In some embodiments, the polymer protective layer is one or more of a polydimethylsiloxane solution, a polyvinylidene fluoride solution, and a polycarbonate solution.

[0031] In some embodiments, the concentrations of the polydimethylsiloxane solution, the polyvinylidene fluoride solution, and the polycarbonate solution are all 100-1000 mg / mL.

[0032] In some embodiments, the solvents used to prepare the polydimethylsiloxane solution, the polyvinylidene fluoride solution, and the polycarbonate solution are all one of chloroform, dichloromethane, toluene, and tetrahydrofuran.

[0033] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0034] The preparation method provided in the present application prepares primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers by a wet spinning method, and chemically crosslinks the primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers under the action of N,N′-carbonyldiimidazole and electrostatically couples them in a cleaning bath, and then performs hot pressing and vacuum drying. On the one hand, a double interface structure of "both a titanium carbide / polyrotaxane dynamic roller skating interface and a titanium carbide / PEDOT rigid interface" can be formed inside the prepared MXene-based fibers. Therefore, when the MXene-based fibers are deformed by stress, the stress can be dissipated based on the roller skating effect generated by the titanium carbide / polyrotaxane dynamic roller skating interface, so that the MXene-based fibers have a stronger deformation bearing capacity, and the MXene-based fibers are endowed with good tensile stability, elongation at break and toughness. When the MXene-based fibers undergo a large deformation, the titanium carbide / PEDOT rigid interface can bear the main The required shear strain makes the MXene-based fibers have excellent mechanical strength and effectively reduces the damage of stress to the conductive rigid network, so that the MXene-based fibers can maintain the structural integrity of the conductive rigid network under high tensile deformation, giving the MXene-based fibers excellent tensile stability, elongation at break, toughness, mechanical strength, electrical conductivity and retention rate of electrical conductivity after cyclic strain; on the other hand, it can form a rich porous structure inside the MXene-based fibers, and the porous structure can serve as an energy dissipator, so that the titanium carbide nanosheets can produce a higher degree of sliding and arrangement in the MXene-based fibers, especially under the combined action of the double interface structure and the porous structure, which effectively increases the axial slip and further orientation of the titanium carbide sheets along the composite fiber, thereby improving the tensile stability, elongation at break, toughness, mechanical strength and electrical conductivity of the prepared MXene-based fibers, while giving the MXene-based fibers excellent softness and high toughness. In addition, since titanium carbide, (PEDOT:PSS) and polyrotaxane can undergo phase separation and shrinkage during wet spinning, the MXene-based fibers form a highly wrinkled structure, which can better deposit functional modifications such as metal nanowire conductive networks and functionalized polymer protective layers, which is beneficial to the preparation of multifunctional ultra-high conductive composite fibers.

[0035] The test results of the embodiment show that the high-performance MXene-based fiber prepared by the preparation method of the present application has a tensile strength of ≥750MPa and a toughness of ≥90MJ / m 3 ; Young's modulus ≤3.5GP; elongation at break ≥20%; conductivity ≥2500S / cm, with better tensile stability, elongation at break, flexibility, mechanical strength, conductivity and conductivity retention rate after cyclic strain. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0037] Figure 1 A planar SEM image of the MXene-based fiber F1 provided in an embodiment of the present application;

[0038] Figure 2 This is a SEM image of the brittle fracture cross section of the MXene-based fiber F1 provided in the embodiment of the present application;

[0039] Figure 3 The brittle fracture cross-section SEM image and the local magnified SEM image of the ultra-high conductive composite fiber SF1 provided in the embodiment of the present application;

[0040] Figure 4 A diagram showing the stretching mechanism of the MXene-based fiber F1 provided in an embodiment of the present application;

[0041] Figure 5 The stress-strain curve of the MXene-based fiber F1 provided in the embodiment of the present application;

[0042] Figure 6 A comparison chart of the electrical conductivity of the MXene-based fiber F1 provided in the embodiment of the present application before and after coating with metal nanowires;

[0043] Figure 7 The resistance change rate during the process of pre-stretching the ultra-high conductive composite fiber SF1 to 20% and then subjecting it to 200,000 cycles of 3% stretching provided in the embodiment of the present application.

[0044] Figure 8 Sewing, weaving and embroidery patterns of MXene-based fiber F1 provided in an embodiment of the present application. DETAILED DESCRIPTION

[0045] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0046] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0047] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0048] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0049] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0050] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be understood as each intermediate value between the upper and lower limits of the scope also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0051] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0052] In a first aspect, the present invention provides a method for preparing a high-performance MXene-based fiber, and the preparation method preferably comprises the following steps:

[0053] Step 1: wet spinning a mixed dispersion containing titanium carbide, (PEDOT:PSS) and polyrotaxane to obtain primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers;

[0054] Step 2: chemically crosslinking the primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber in an organic solvent containing N,N′-carbonyldiimidazole to obtain a MXene-based fiber with a dynamic roller-slip interface structure;

[0055] Step 3: After electrostatically coupling the MXene-based fiber with a dynamic roller skating interface structure in a cleaning bath, hot pressing and vacuum drying are performed in sequence to obtain high-performance MXene-based fibers.

[0056] Among them, the preparation method provided in the embodiment of the present application firstly adds (PEDOT:PSS) as a spinning dispersion to the liquid crystal mixed dispersion of titanium carbide and polyrotaxane, and prepares a primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber with a highly wrinkled surface by wet spinning, and the highly wrinkled structure on the surface can better deposit functional modified materials such as metal nanowire conductive network and functionalized polymer protective layer, thereby facilitating the preparation of multifunctional ultra-high conductive composite fibers; secondly, the primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers are cross-linked with N,N′-carbonyldiimidazole in turn, so that the titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers are cross-linked with N,N′-carbonyldiimidazole in turn, so that the titanium carbide / (PEDOT: The titanium carbide and polyrotaxane in the titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber structure are chemically cross-linked to form a titanium carbide / polyrotaxane dynamic roller skating interface, and, after immersion in a cleaning bath, the PSS in the titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber structure is precipitated and electrostatic coupling between titanium carbide and PEDOT is promoted to form a titanium carbide / PEDOT rigid interface. When the MXene-based fiber is stretched and deformed under stress, the cross-linking points between the titanium carbide / polyrotaxane dynamic roller skating interface can cooperate with the stretching of the polyrotaxane molecular chain to make α-cyclodextrin slide along the main chain of the polyethylene glycol molecule, generating a roller skating effect to dissipate stress, thereby achieving It mainly bears the role of tensile deformation, so that the MXene-based fiber has good tensile stability, elongation at break and toughness. When the MXene-based fiber undergoes a larger deformation, the titanium carbide / PEDOT rigid interface can be used as a stress bearing point to bear the main shear strain, which makes the MXene-based fiber have excellent mechanical strength and reduces the damage of stress to the conductive rigid network. The MXene-based fiber can maintain the integrity of the conductive rigid network structure under high tensile deformation, giving the MXene-based fiber excellent tensile stability, elongation at break, toughness, mechanical strength, conductivity and conductivity retention rate after cyclic strain; finally, the fiber is subjected to fiber hot pressing technology and vacuum The drying treatment further optimizes and regulates the porous structure within the MXene-based fiber structure. The microporous structure can not only act as a "plasticizer" to soften the MXene-based fiber material, making the composite fiber have excellent softness and toughness, and excellent weaving properties, but also can act as an energy dissipator, allowing the titanium carbide nanosheets to produce a higher degree of sliding and arrangement in the MXene-based fibers, further promoting the axial sliding and orientation of the titanium carbide sheets along the composite fibers, so that the MXene-based fibers have excellent tensile stability, elongation at break, toughness, mechanical strength, and electrical conductivity, while giving the MXene-based fibers excellent softness and high toughness.

[0057] It should be noted that the titanium carbide / polyrotaxane cross-linked interface refers to the chemical covalent bond formed by the chemical cross-linking reaction between the α-cyclodextrin with hydroxyl groups on the polyrotaxane and the hydroxyl groups on the surface of the titanium carbide sheet through N,N′-carbonyldiimidazole; the titanium carbide / PEDOT rigid interface refers to the MXene-based fiber with a dynamic roller skating interface structure. When it is immersed in a cleaning bath, as PSS precipitates, the Ti-OH on the surface of the titanium carbide sheet replaces the position of PSS and undergoes a strong electrostatic coupling with PEDOT to form a titanium carbide / PEDOT rigid interface.

[0058] As an example description, the present application embodiment provides a method for preparing a mixed dispersion containing titanium carbide, (PEDOT:PSS) and polyrotaxane, and the preparation method preferably includes:

[0059] Dispersing titanium carbide nanosheets in water to obtain a titanium carbide liquid crystal aqueous dispersion having a concentration of 80 to 200 mg / mL;

[0060] The titanium carbide liquid crystal aqueous dispersion is mixed with a (PEDOT:PSS) aqueous dispersion to obtain a titanium carbide / (PEDOT:PSS) liquid crystal mixed aqueous dispersion having a concentration of 80 to 200 mg / mL, wherein the mass fraction of the (PEDOT:PSS) in the titanium carbide is 0.5 to 15%;

[0061] Synthesizing a polyrotaxane material according to a method known in the art, and preparing a polyrotaxane aqueous dispersion with a concentration of 30 to 200 mg / mL;

[0062] The titanium carbide / (PEDOT:PSS) liquid crystal mixed aqueous dispersion and the polyrotaxane aqueous dispersion are mixed to obtain a titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal mixed dispersion with a concentration of 80 to 200 mg / mL, wherein the mass fraction of polyrotaxane in titanium carbide is 5 to 30%, and the mass fraction of (PEDOT:PSS) in titanium carbide is 0.5 to 15%.

[0063] It should be noted that the (PEDOT:PSS) is understood according to the general chemical meaning of the relevant field, and the embodiments of the present application are not repeated here; at the same time, the concentration and mass fraction described above should be understood to include any one of the ranges, for example, 80-200 mg / mL is represented by 80 mg / mL, 100 mg / mL, 120 mg / mL, 150 mg / mL, 180 mg / mL, 200 mg / mL or any integer or non-integer in the range of 80 to 200; 0.5-15% is represented by 0.5%, 1%, 1.5%, 3%, 5%, 10%, 12%, 15% or any integer or non-integer in the range of 0.5 to 15. Of course, other concentrations or mass fractions are also understood according to the example description, and the embodiments of the present application are no longer described one by one.

[0064] As an example description, an embodiment of the present application provides a wet spinning operation process, namely: an aqueous dispersion containing titanium carbide, (PEDOT:PSS) and polyrotaxane is extruded through a spinning die, coagulated in a poor solvent coagulation bath and collected by a roller to obtain primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers.

[0065] It should be noted that the specific operating parameters of the spinning die, coagulation and roller collection are not particularly limited in the embodiments of the present application, and those skilled in the art can set them according to actual needs. Among them, the coagulation bath is preferably an acetic acid solution, a chitosan solution, a mixed solution of acetic acid and dimethyl sulfoxide (mixed volume ratio of 1:1 to 40:1), and an ethanol / water solution of magnesium sulfate (solvent volume ratio of 1:1 to 10:1, and the mass fraction of magnesium sulfate is 0.1 to 2%).

[0066] In some example descriptions, the polyrotaxane is preferably at least one of polyisoprene / α-cyclodextrin, poly(ethylene glycol) / α-cyclodextrin, poly(propylene oxide) / α-cyclodextrin, poly(ethylene oxide) / α-cyclodextrin, N-[tris(hydroxymethyl)methyl]acrylamide / α-cyclodextrin or methacrylate-2-hydroxyethyl ester / α-cyclodextrin.

[0067] It should be noted that the coverage of the α-cyclodextrin is preferably 0.2-10%, such as 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5% or any one within the range. In particular, the embodiment of the present application can effectively regulate the slip space of the α-cyclodextrin along the main chain of the polyethylene glycol molecule by controlling the coverage of the α-cyclodextrin, thereby ensuring sufficient roller skating effect.

[0068] In some example descriptions, when the primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber is chemically cross-linked in an organic solvent containing N,N′-carbonyldiimidazole, the temperature is controlled to be 50-80°C and the time is 10-60 minutes. The temperature is preferably 50°C, 60°C, 70°C, 80°C or any one of the ranges; the time is preferably 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes or any one of the ranges.

[0069] It should be noted that the embodiment of the present application controls the temperature and time of chemical crosslinking to ensure that the titanium carbide nanosheets and polyrotaxane undergo a rapid and complete chemical crosslinking reaction, so that a stable titanium carbide / polyrotaxane dynamic pulley interface is formed inside the composite fiber.

[0070] In some example descriptions, the mass fraction of the N,N′-carbonyldiimidazole in the organic solvent is 0.3-8wt%, preferably 0.3wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt% or any one within the range. In this embodiment of the present application, by controlling the mass fraction of N,N′-carbonyldiimidazole, a moderate cross-linking reaction between titanium carbide and polyrotaxane occurs, and an excessive cross-linking network hinders the slip of α-cyclodextrin, weakens the dissipation and transmission of external energy by the dynamic pulley interface structure, and results in smaller stress and strain.

[0071] In some example descriptions, the electrostatic coupling time of the MXene-based fiber with a dynamic roller skating interface structure in the cleaning bath is controlled to be 10 to 50 minutes. Among them, the time is preferably 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes or any one within the range. The embodiment of the present application controls the time of electrostatic coupling so that PSS is fully precipitated, ensuring that the Ti-OH on the surface of the titanium carbide layer fully replaces the position of PSS, and has a strong electrostatic coupling effect with PEDOT to form a stable titanium carbide / PEDOT rigid interface.

[0072] In some example descriptions, the cleaning bath is preferably any one of a dimethyl sulfoxide solution, a methanol solution, a 0.1-5M sulfuric acid aqueous solution, and a methanol / ethanol mixed solution (mixed volume ratio of 1:1 to 50:1). Among them, these cleaning baths are good solvents for PSS, which are conducive to the precipitation of PSS. In the embodiment of the present application, the MXene-based fiber with a dynamic roller skating interface structure is immersed in the solution. As the PSS gradually precipitates, the Ti-OH on the surface of the titanium carbide layer replaces the position of PSS and has a strong electrostatic coupling with PEDOT, forming a titanium carbide / PEDOT rigid interface.

[0073] In some example descriptions, the hot pressing temperature for the hot pressing is 40-120°C, the hot pressing pressure is 0.5-15kPa, and the holding time is 3-30 minutes. The hot pressing temperature is preferably 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or any one in the range; the hot pressing pressure is preferably 0.5kPa, 1kPa, 1.5kPa, 2kPa, 5kPa, 15kPa or any one in the range; the holding time is preferably 3 minutes, 5 minutes, 10 minutes, 20 minutes, 20 minutes or any one in the range.

[0074] It should be noted that the embodiments of the present application can effectively regulate the micropore structure in the prepared MXene-based fibers by controlling the hot pressing operation, so that the MXene-based fibers contain adjustable micropores, which can not only act as a plasticizer to soften the MXene-based fiber material, but also act as an energy dissipator to provide a higher degree of sliding and arrangement of titanium carbide nanosheets in the MXene-based fibers, thereby strengthening and toughening the MXene-based fiber material, so that the MXene-based fibers have excellent softness and toughness.

[0075] In some example descriptions, the vacuum drying is performed at a temperature of 90 to 180°C and for a time of 20 to 100 minutes. Preferably, the vacuum drying is performed at 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or any one of the above ranges; and the time is preferably 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes or any one of the above ranges.

[0076] On the second aspect, the embodiments of the present application provide high-performance MXene-based fibers prepared by the preparation method of the present application. Among them, based on the preparation method of the embodiments of the present application, a clear wrinkle structure can be constructed on the surface of the MXene-based fiber, and a double interface structure of "combining titanium carbide / polyrotaxane cross-linked interface and titanium carbide / PEDOT rigid interface" and a rich porous structure can be formed in the MXene-based fiber structure. On the one hand, based on the wrinkle structure on the surface, better deposition of functionalized modifiers such as metal nanowire conductive networks and functionalized polymer protective layers can be achieved; on the other hand, based on the synergistic effect between the double interface structures in the MXene-based fiber structure and the synergistic effect between the double interface structure and the rich porous structure, the composite fiber of the embodiment of the present application has better tensile stability, elongation at break, flexibility, mechanical strength, electrical conductivity and retention rate of electrical conductivity after cyclic strain.

[0077] Among them, the test results of the embodiment show that the high-performance MXene-based fiber of the embodiment of the present application has at least one of the following characteristics:

[0078] Tensile strength ≥750MPa; Toughness ≥90MJ / m 3 ;

[0079] Young's modulus ≤3.5GPa; elongation at break ≥20%;

[0080] Conductivity ≥2500S / cm.

[0081] In the third aspect, the embodiments of the present application provide the application of the high-performance MXene-based fibers of the embodiments of the present application for preparing multifunctional ultra-high conductive composite fibers. Among them, the MXene-based fibers based on the embodiments of the present application have better tensile stability, elongation at break, tensile strength, flexibility, conductivity, and retention rate of conductivity after cyclic strain. Therefore, when used to prepare multifunctional ultra-high conductive composite fibers, the multifunctional ultra-high conductive composite fibers can have better conductivity while showing excellent tensile stability, elongation at break, tensile strength, flexibility, conductivity, and retention rate of conductivity after cyclic strain.

[0082] In a fourth aspect, the present application also provides a method for preparing a multifunctional ultra-high conductive composite fiber, which preferably includes:

[0083] The high-performance MXene-based fiber is immersed in a 0.2-3 wt% metal nanowire solution, and then taken out and dried to obtain an ultra-high conductive composite fiber;

[0084] Coating a polymer protective layer on the surface of the ultra-high conductive composite fiber to obtain a multifunctional ultra-high conductive composite fiber;

[0085] Wherein, the ultra-high conductive composite fiber has at least one of the following characteristics:

[0086] Conductivity is 100000~120000S / cm;

[0087] The conductivity retention after 200,000 stretching cycles is >95%.

[0088] It should be noted that, in the embodiment of the present application, the high-performance MXene-based fibers are immersed in a 0.2-3wt% metal nanowire solution and then directly coated with a polymer protective layer, so that the high-performance MXene-based fibers are compounded with metal nanowires and the polymer protective layer in sequence, thereby further greatly improving the electrical conductivity based on the synergistic effect of the metal nanowires and the high-performance MXene-based fibers, and giving it functions such as spinnability and washability based on the polymer protective layer.

[0089] In some example descriptions, the metal nanowires are preferably one or a combination of gold nanowires, silver nanowires, copper nanowires or platinum nanowires.

[0090] In some example descriptions, the polymer protective layer is preferably one or more of polydimethylsiloxane solution, polyvinylidene fluoride solution, and polycarbonate solution.

[0091] In some example descriptions, the mass concentrations of the polydimethylsiloxane solution, polyvinylidene fluoride solution and polycarbonate solution are all 100-1000 mg / mL, and may be preferably 100 mg / mL, 200 mg / mL, 300 mg / mL, 400 mg / mL, 500 mg / mL, 600 mg / mL, 700 mg / mL, 800 mg / mL, 900 mg / mL, 1000 mg / mL or any one within the said range.

[0092] In some exemplary descriptions, the solvent used to prepare the polydimethylsiloxane solution, the polyvinylidene fluoride solution and the polycarbonate solution is preferably one of chloroform, dichloromethane, toluene and tetrahydrofuran.

[0093] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0094] Example 1

[0095] This embodiment provides a method for preparing a multifunctional ultra-high conductive composite fiber MSF1, comprising the following steps:

[0096] Step 1: Weigh 0.15 g of titanium carbide with a sheet size of about 1 to 2 μm into a beaker, add 10 mL of deionized water, and sonicate for 20 minutes to obtain a uniformly dispersed titanium carbide dispersion. After centrifugal enrichment and constant volume, 150 mg / mL of Ti3C2T X Dispersion liquid;

[0097] Step 2: After concentrating and filtering (PEDOT:PSS), add it to the Ti3C2T x The dispersion was vortexed at room temperature for 3 hours to obtain a titanium carbide / (PEDOT:PSS) mixed dispersion, wherein the solid content of (PEDOT:PSS) was 10.5 mg;

[0098] Step 3: Weigh 30 mg of polyisoprene / α-cyclodextrin (α-cyclodextrin coverage is 3%) and add it to 200 μL of water, and ultrasonicate for 20 minutes to obtain a 300 mg / mL polyrotaxane dispersion;

[0099] Step 4: adding the polyrotaxane dispersion to the titanium carbide / (PEDOT:PSS) mixed dispersion, vortexing at room temperature for 3 hours to obtain a titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal mixed dispersion;

[0100] Step 5: Extruding the titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal dispersion through a spinning die, coagulating in an acetic acid coagulation bath, and collecting on a roller to obtain primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers;

[0101] Step 6: dissolving 0.45 g of N,N′-carbonyldiimidazole in 15 mL of dimethyl sulfoxide to form an N,N′-carbonyldiimidazole crosslinking bath, and immersing the primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber in the N,N′-carbonyldiimidazole crosslinking bath at 50° C. for 40 minutes to obtain a MXene-based fiber with a dynamic roller skating interface structure;

[0102] Step 7: After soaking the MXene-based fiber with a dynamic roller skating interface structure in a methanol cleaning bath for 20 minutes, the fiber was transferred to a hot pressing device at 70° C. and hot pressed at a pressure of 1 kPa for 6 minutes. After being collected, the fiber was placed in a 130° C. oven for vacuum heating and drying for 80 minutes to obtain a MXene-based fiber F1 having a porosity of 50%;

[0103] Step 8: Soak the MXene-based fiber F1 in an ethanol bath containing 0.8 wt% gold nanowires for 15 minutes, and then vacuum dry it in a 60° C. heating device for 10 minutes. Repeat this operation 3 times to obtain an ultra-high conductive composite fiber SF1.

[0104] Step nine: evenly coating the surface of the ultra-high conductive composite fiber with a 100 mg / mL polydimethylsiloxane / tetrahydrofuran solution to obtain a multifunctional ultra-high conductive composite fiber MSF1.

[0105] In order to illustrate the structural properties of the MXene-based fibers, ultrahigh conductive composite fibers, and multifunctional ultrahigh conductive composite fibers prepared in the examples of the present application, the structural properties of the related products prepared in Example 1 are characterized as follows:

[0106] 1. Planar characterization of MXene-based fibers

[0107] Figure 1 A plan SEM image of MXene-based fiber F1 is shown.

[0108] according to Figure 1 It can be seen that an obvious wrinkled structure is formed on the surface of the titanium carbide composite conductive fiber F1, which can better deposit the metal nanowire conductive network and facilitate the coating of the polymer.

[0109] 2. Characterization of brittle fracture cross section of MXene-based fiber F1

[0110] Figure 2 The SEM image of the brittle fracture cross section of MXene-based fiber F1 is shown.

[0111] according to Figure 2It can be seen that the cross-section of the MXene-based fiber F1 layer is densely stacked and has an obvious microporous structure. The microporous structure can not only act as a "plasticizer" to soften the composite fiber, making the MXene-based fiber have excellent weaving properties, but also act as an energy dissipator, allowing the titanium carbide nanosheets to produce a higher degree of sliding and arrangement in the composite fiber, further promoting the axial sliding and further orientation of the titanium carbide layer along the composite fiber, giving the MXene-based fiber excellent tensile stability, elongation at break, flexibility, mechanical strength, electrical conductivity and conductivity retention rate after cyclic strain.

[0112] 3. Characterization of brittle fracture cross section of ultra-high conductive composite fiber SF1

[0113] Figure 3 The brittle fracture cross-section SEM image and the locally enlarged SEM image of the ultra-high conductive composite fiber SF1 are shown, wherein a is the brittle fracture cross-section SEM image of the ultra-high conductive composite fiber SF1; b is the locally enlarged SEM image in a.

[0114] according to Figure 3 It can be seen that a uniform silver nanowire conductive network is formed on the surface of the ultrahigh conductive composite fiber SF1, indicating that the highly wrinkled structure on the surface of the MXene-based fiber F1 is conducive to better deposition of the silver nanowire conductive network.

[0115] 4. Stretching mechanism of MXene-based fiber F1

[0116] Figure 4 A diagram showing the stretching mechanism of MXene-based fiber F1.

[0117] according to Figure 4 It can be seen that a chemical bond is formed between the Ti-OH of titanium carbide and the cyclodextrin of polyrotaxane, forming a slippable dynamic wheel-slip interface of titanium carbide / polyrotaxane, while the Ti-OH of titanium carbide and PEDOT form a rigid interface of titanium carbide / PEDOT through electrostatic coupling. When the titanium carbide conductive fiber is subjected to tensile deformation under stress, the cross-linking points between the dynamic wheel-slip interface of titanium carbide and polyrotaxane cooperate with the stretching of the polyrotaxane molecular chain, causing α-cyclodextrin to slide along the main chain of polyethylene glycol molecules, resulting in a wheel-slip effect, dissipating stress, and mainly bearing tensile strain; when the composite fiber undergoes a large deformation, the stress is mainly concentrated on the rigid interface of titanium carbide / PEDOT, bearing the main shear strain. Based on this dual interface structure, the titanium carbide layer is simultaneously promoted to slide and further orient along the fiber axis, which is of great significance for improving the tensile stability, elongation at break, flexibility, mechanical strength, conductivity, and conductivity retention rate after cyclic strain of MXene-based fibers.

[0118] 5. Mechanical properties test of MXene-based fiber F1

[0119] This application tests the mechanical properties of MXene-based fiber F1 through stress-strain curves, and the results are Figure 5 As shown. Among them, Figure 5 The stress-strain curve of MXene-based fiber F1 is shown.

[0120] according to Figure 5 It can be seen that the tensile strength of MXene-based fiber F1 is 1100MPa, the elongation at break is 34%, and the toughness is 140MJ / m 3 , and the Young’s modulus is 2.1 GPa, indicating that the MXene-based fiber F1 has excellent mechanical properties and a low Young’s modulus. The low Young’s modulus indicates that the fiber has excellent flexibility, which is beneficial to the weaving of the fiber.

[0121] 6. Conductivity Characterization

[0122] Figure 6 A comparison of the electrical conductivity of MXene-based fiber F1 before and after coating with metal nanowires is shown.

[0123] according to Figure 6 It can be seen that the electrical conductivity of MXene-based fiber F1 is 5000S / cm. After being coated with metal nanowires, the electrical conductivity is significantly improved to as high as 120000S / cm.

[0124] 7. Tensile stability and tensile cycle stability test

[0125] In order to verify the tensile stability and tensile cycle stability of the ultra-high conductive composite fiber SF1, we first pre-stretched the fiber to a strain of 20%, and then performed a 3% tensile cycle for 200,000 cycles at this strain, and tested the resistance change rate during the stretching cycle. The results were Figure 7 As shown. Among them, Figure 7 The resistance change rate during 200,000 stretching cycles of 3% after the ultra-high conductive composite fiber SF1 was pre-stretched to 20%.

[0126] according to Figure 7 It can be seen that the conductivity retention rate after 200,000 stretching cycles is >95%, showing ultra-high structural stability.

[0127] 8. Weavable performance test

[0128] The figure shows the sewing, weaving and embroidery diagram of MXene-based fiber F1.

[0129] according to Figure 8 It can be seen that MXene-based fiber F1 has excellent toughness and can be sewn, woven and embroidered at will without breaking.

[0130] Example 2

[0131] This embodiment provides a method for preparing a multifunctional ultra-high conductive composite fiber MSF2, comprising the following steps:

[0132] Step 1: Weigh 0.17 g of titanium carbide with a layer size of about 1 to 2 μm into a beaker, add 10 mL of deionized water, and sonicate for 20 minutes to obtain a uniformly dispersed titanium carbide dispersion. After centrifugal enrichment and constant volume, 170 mg / mL of Ti3C2T X Dispersion liquid;

[0133] Step 2: After concentrating and filtering (PEDOT:PSS), add it to the Ti3C2T x The dispersion was vortexed at room temperature for 3 hours to obtain a titanium carbide / (PEDOT:PSS) mixed dispersion, wherein the solid content of (PEDOT:PSS) was 8.5 mg;

[0134] Step 3: Weigh 34 mg of poly(ethylene glycol) / α-cyclodextrin (α-cyclodextrin coverage is 2.5%) and add it to 200 μL of water. Ultrasonicate for 20 minutes to obtain a 170 mg / mL polyrotaxane dispersion.

[0135] Step 4: adding the polyrotaxane dispersion to the titanium carbide / (PEDOT:PSS) mixed dispersion, vortexing at room temperature for 3 hours to obtain a titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal mixed dispersion;

[0136] Step 5: Extruding the titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal dispersion through a spinning die, coagulating in an acetic acid coagulation bath, and collecting on a roller to form titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers;

[0137] Step 6: dissolving 0.3 g of N,N′-carbonyldiimidazole in 15 mL of dimethyl sulfoxide to form N,N′-carbonyldiimidazole, and immersing the primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber in a 60° C. N,N′-carbonyldiimidazole crosslinking bath for 35 minutes to obtain a MXene-based fiber with a dynamic roller skating interface structure;

[0138] Step 7: After the MXene-based fiber with a dynamic roller skating interface structure is immersed in a 1M sulfuric acid cleaning bath for 15 minutes, it is transferred to a hot pressing device at 60°C and hot pressed at a pressure of 0.5 kPa for 6 minutes. After being collected, it is placed in a 130°C oven for vacuum heating and drying for 80 minutes to obtain a MXene-based fiber F2 with a porosity of 56%, an electrical conductivity of 4800 S / cm, a tensile strength of 1164 MPa, an elongation at break of 32%, and a toughness of 137 MJ / m 3 , Young’s modulus is 1.5 GPa;

[0139] Step 8: Soak the MXene-based fiber F2 in an ethanol bath containing 1 wt% silver nanowires for 10 minutes, and then vacuum dry it in a 50°C heating device for 8 minutes. Repeat this operation 3 times to obtain an ultra-high conductive composite fiber SF2 with a conductivity of 115,000 S / cm.

[0140] Step nine: evenly coating the surface of the ultra-high conductive composite fiber with a 300 mg / mL polyvinylidene fluoride / toluene solution to obtain a multifunctional ultra-high conductive composite fiber MSF2.

[0141] Example 3

[0142] This embodiment provides a method for preparing a multifunctional ultra-high conductive composite fiber MSF3, comprising the following steps:

[0143] Step 1: Weigh 0.12g of titanium carbide with a layer size of about 1-2μm into a beaker, add 10mL of deionized water, and sonicate for 20 minutes to obtain a uniformly dispersed titanium carbide dispersion. After centrifugal enrichment and constant volume, 120mg / mL of Ti3C2T X Dispersion liquid;

[0144] Step 2: After concentrating and filtering (PEDOT:PSS), add it to the Ti3C2T x The dispersion was vortexed at room temperature for 3 hours to obtain a titanium carbide (PEDOT:PSS) mixed dispersion, wherein the solid content of (PEDOT:PSS) was 6 mg;

[0145] Step 3: Weigh 30 mg of poly(propylene oxide) / α-cyclodextrin (α-cyclodextrin coverage is 5%) and add it to 200 μL of water, and sonicate for 20 minutes to obtain a 150 mg / mL polyrotaxane dispersion;

[0146] Step 4: adding the polyrotaxane dispersion to the titanium carbide / (PEDOT:PSS) mixed dispersion, vortexing at room temperature for 3 hours to obtain a titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal mixed dispersion;

[0147] Step 5: Extruding the titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal dispersion through a spinning die, coagulating in an acetic acid / dimethyl sulfoxide (volume ratio of 10:1) coagulation bath, and collecting on a roller to obtain primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers;

[0148] Step 6: dissolving 0.4 g of N,N′-carbonyldiimidazole in 20 mL of dimethyl sulfoxide to form an N,N′-carbonyldiimidazole crosslinking bath, and immersing the primary titanium carbide (PEDOT:PSS) / polyrotaxane composite fiber in the N,N′-carbonyldiimidazole crosslinking bath at 70° C. for 10 minutes to obtain a MXene-based fiber with a dynamic roller skating interface structure;

[0149] Step 7: After soaking the MXene-based fiber with a dynamic roller skating interface structure in a methanol cleaning bath for 20 minutes, the fiber was transferred to a hot pressing device at 80°C, hot pressed at a pressure of 15 kPa for 6 minutes, collected and placed in a 130°C oven for vacuum heating and drying for 80 minutes to obtain a MXene-based fiber F3 having a porosity of 15%, an electrical conductivity of 3500 S / cm, a tensile strength of 753 MPa, an elongation at break of 26%, and a toughness of 90 MJ / m 3 , Young’s modulus is 3.5 GPa;

[0150] Step 8: Soak the MXene-based fiber F3 in an ethanol bath containing 1.2 wt% copper nanowires for 10 minutes, and then vacuum dry it in a 50°C heating device for 8 minutes. Repeat this operation 3 times to obtain an ultra-high conductive composite fiber SF3 with a conductivity of 100,000 S / cm.

[0151] Step nine: 400 mg / mL polycarbonate / tetrahydrofuran is evenly coated on the surface of the ultra-high conductive composite fiber to obtain a multifunctional ultra-high conductive composite fiber MSF3.

[0152] Example 4

[0153] This embodiment provides a method for preparing a multifunctional ultra-high conductive composite fiber MSF4, comprising the following steps:

[0154] Step 1: Weigh 0.15 g of titanium carbide with a sheet size of about 1 to 2 μm into a beaker, add 10 mL of deionized water, and sonicate for 20 minutes to obtain a uniformly dispersed titanium carbide dispersion. After centrifugal enrichment and constant volume, 150 mg / mL of Ti3C2T X Dispersion liquid;

[0155] Step 2: After concentrating and filtering (PEDOT:PSS), add it to the Ti3C2T x The dispersion was vortexed at room temperature for 3 hours to obtain a titanium carbide / (PEDOT:PSS) mixed dispersion, wherein the solid content of (PEDOT:PSS) was 10.5 mg;

[0156] Step 3: Weigh 30 mg of poly(ethylene glycol) / α-cyclodextrin (α-cyclodextrin coverage is 4%) and add it to 200 μL of water, and sonicate for 20 minutes to obtain a 150 mg / mL polyrotaxane dispersion;

[0157] Step 4: adding the polyrotaxane dispersion to the titanium carbide / (PEDOT:PSS) mixed dispersion, vortexing at room temperature for 3 hours to obtain a titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal mixed dispersion;

[0158] Step 5: Extruding the titanium carbide / (PEDOT:PSS) / polyrotaxane liquid crystal dispersion through a spinning die, coagulating in an acetic acid coagulation bath, and collecting on a roller to obtain primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers;

[0159] Step 6: dissolving 0.25 g of N,N′-carbonyldiimidazole in 15 mL of dimethyl sulfoxide to form an N,N′-carbonyldiimidazole crosslinking bath, and immersing the titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber in the N,N′-carbonyldiimidazole crosslinking bath at 55° C. for 35 minutes to obtain a MXene-based fiber with a dynamic roller skating interface structure;

[0160] Step 7: After soaking the MXene-based fiber with a dynamic roller skating interface structure in a methanol cleaning bath for 20 minutes, the fiber was transferred to a hot pressing device at 80°C, hot pressed at a pressure of 1 kPa for 6 minutes, collected and placed in a 130°C oven for vacuum heating and drying for 80 minutes to obtain a MXene-based fiber F4 with a porosity of 48%, a conductivity of 4500 S / cm, a tensile strength of 917 MPa, an elongation at break of 30%, and a toughness of 110 MJ / m 3 , Young’s modulus is 2.3 GPa;

[0161] Step 8: Soak the MXene-based fiber F1 in an ethanol bath containing 1 wt% platinum nanowires for 10 minutes, and then vacuum dry it in a 50°C heating device for 8 minutes. Repeat this operation 3 times to obtain an ultra-high conductive composite fiber SF4 with a conductivity of 108900 S / cm.

[0162] Step nine: evenly coating the surface of the ultra-high conductive composite fiber with a 500 mg / mL polyvinylidene fluoride / tetrahydrofuran solution to obtain a multifunctional ultra-high conductive composite fiber MSF4.

[0163] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0164] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A method for preparing high-performance MXene-based fibers, characterized in that: include: Wet spinning a mixed dispersion containing titanium carbide, (PEDOT:PSS) and polyrotaxane to obtain primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fibers, wherein the mass fraction of polyrotaxane in titanium carbide is 5-30%, and the mass fraction of (PEDOT:PSS) in titanium carbide is 0.5-15%; The primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber is chemically cross-linked in an organic solvent containing N,N′-carbonyldiimidazole to obtain a MXene-based fiber with a dynamic roller-slip interface structure; The MXene-based fiber with a dynamic roller-skating interface structure is electrostatically coupled in a cleaning bath, and then hot-pressed and vacuum-dried in sequence to obtain a high-performance MXene-based fiber; The electrostatic coupling time is controlled to be 10 to 50 minutes, and the cleaning bath is any one of a dimethyl sulfoxide solution, a methanol solution, a 0.1 to 5 M sulfuric acid aqueous solution, and a methanol / ethanol mixed solution; The hot pressing temperature of the hot pressing is 40-120° C., the hot pressing pressure is 0.5-15 kPa, and the holding time is 3-30 minutes.

2. The preparation method according to claim 1, characterized in that: The polyrotaxane is one or more of polyisoprene / α-cyclodextrin, poly(ethylene glycol) / α-cyclodextrin, poly(propylene oxide) / α-cyclodextrin, poly(ethylene oxide) / α-cyclodextrin, N-[tri(hydroxymethyl)methyl]acrylamide / α-cyclodextrin or methacrylate-2-hydroxyethyl ester / α-cyclodextrin, wherein the coverage of the α-cyclodextrin is 0.2-10%.

3. The preparation method according to claim 1, characterized in that: When the primary titanium carbide / (PEDOT:PSS) / polyrotaxane composite fiber is chemically cross-linked in an organic solvent containing N,N′-carbonyldiimidazole, the temperature is controlled to be 50-80° C. and the time is 10-60 minutes; And / or, the mass fraction of the N,N′-carbonyldiimidazole in the organic solvent is 0.3-8 wt %.

4. The preparation method according to claim 1, characterized in that: The vacuum drying is performed at a temperature of 90 to 180° C. and a time of 20 to 100 minutes.

5. A high-performance MXene-based fiber prepared according to the preparation method according to any one of claims 1 to 4, characterized in that: The high-performance MXene-based fiber has at least one of the following characteristics: Tensile strength ≥750MPa; Toughness ≥90MJ / m 3 ; Young's modulus ≤3.5GPa; elongation at break ≥20%; Conductivity ≥2500S / cm.

6. Use of the high-performance MXene-based fiber prepared by the preparation method according to any one of claims 1 to 4 in the preparation of multifunctional ultra-high conductive composite fibers.

7. A method for preparing a multifunctional ultra-high conductive composite fiber, characterized in that: include: The high-performance MXene-based fiber prepared by the preparation method according to any one of claims 1 to 4 is immersed in a 0.2-3 wt % metal nanowire solution, and then taken out and dried to obtain an ultra-high conductive composite fiber; Coating a polymer protective layer on the surface of the ultra-high conductive composite fiber to obtain a multifunctional ultra-high conductive composite fiber; Wherein, the ultra-high conductive composite fiber has the following characteristics: Conductivity is 100000~200000S / cm; The conductivity retention after 200,000 stretching cycles is >95% S / cm.

8. The preparation method according to claim 7, characterized in that: The metal nanowires are one or a combination of gold nanowires, silver nanowires, copper nanowires or platinum nanowires; And / or, the polymer protective layer is one or more of polydimethylsiloxane solution, polyvinylidene fluoride solution, and polycarbonate solution; and / or, the concentrations of the polydimethylsiloxane solution, the polyvinylidene fluoride solution and the polycarbonate solution are all 100-1000 mg / mL; And / or, the solvents used to prepare the polydimethylsiloxane solution, the polyvinylidene fluoride solution and the polycarbonate solution are all one of chloroform, dichloromethane, toluene and tetrahydrofuran.

Citation Information

Patent Citations

  • A method for preparing mechanically interlocked high-performance titanium carbide composite conductive fibers

    CN115537972B

  • Novel perovskite battery and preparation method thereof

    CN111081881A

  • Preparation method of flexible stress sensor with multi-dimensional microstructure

    CN112146798A